Natural and artificial intelligence : misconceptions about brains and neural networks - Callatay, Armand M. de, 1935- (North-Holland, 1992)
How does the mind work? How is data stored in the brain? How does the mental world connect with the physical world? The hybrid system developed in this book shows a radically new view on the brain. Briefly, in this model memory remains permanent by changing the homeostasis rebuilding the neuronal organelles. These transformations are approximately abstracted as all-or-none operations. Thus the computer-like neural systems become plausible biological models. This illustrated book shows how artificial animals with such brains learn invariant methods of behavior control from their repeated actions. These robots can make decisions in any circumstances and reason by analogy whenever possible.